Effectiveness of reciprocal methods on basic skills in playing football: An experimental study - Rusmanto; Lardika, Rola Angga; Muspita (Edu Sportivo: Indonesian Journal of Physical Education, 2020)
The purpose of this study is to reveal the effect of the reciprocal method on the basic skills of playing Football. This type of research is quasi-experimental, the study population was 57 male students of SMP Negeri 2 Bunut Pelalawan Regency, Riau Province, while the sample in this study was 40 students after using purposive sampling technique. The research instrument used was the David Lee proficiency test which was a development of David Lee made by Subagyo Irianto. Data were analyzed using statistical normality test and t-test. The results of data analysis showed that there was a significant influence of reciprocal methods on the basic skills of playing soccer for students of SMP Negeri 2 Bunut, Pelalawan Regency, Riau Province.